2015
DOI: 10.1007/s12560-015-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of Classical Human Astrovirus in Uruguay

Abstract: The aim of this study was to determine the molecular epidemiology of classical human astrovirus (HAstV) strains in sewage samples from four Uruguayan cities: Bella Unión, Salto, Paysandú, and Fray Bentos, located in the Northwestern region of the country. Overall, 96 sewage samples were collected biweekly between March 2011 and February 2012 and were subject to ultracentrifugation methodology in order to concentrate the viruses. RT-PCR directed to the ORF2 genome region was performed followed by sequencing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…The predominant HAstV genotype from WWTP effluents was clearly HAstV-1, which was in agreement with the findings of many epidemiological studies (38)(39)(40). Previous studies also detected HAstV-2 and/or HAstV-5 in environmental water samples (38,41); however, to our knowledge, this is the first time that HAstV-6 has been detected in WWTP effluents. In opposition, the predominant genotype from stool samples collected was HAstV-5, following by HAstV-2.…”
Section: Discussionsupporting
confidence: 91%
“…The predominant HAstV genotype from WWTP effluents was clearly HAstV-1, which was in agreement with the findings of many epidemiological studies (38)(39)(40). Previous studies also detected HAstV-2 and/or HAstV-5 in environmental water samples (38,41); however, to our knowledge, this is the first time that HAstV-6 has been detected in WWTP effluents. In opposition, the predominant genotype from stool samples collected was HAstV-5, following by HAstV-2.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the recently identified MLB-1 HAstV was detected and characterized for the first time in sewage in a Latin American country. At the same time, the presence in Uruguay of classical HAstV genotypes in the environment was confirmed as previously reported (Lizasoain et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, the presence in Uruguay of classical HAstV genotypes in the environment was confirmed as previously reported (Lizasoain et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations